2022
DOI: 10.3390/bioengineering9010013
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic and Thermophilic Anaerobic Digestion of Wheat Straw in a CSTR System with ‘Synthetic Manure’: Impact of Nickel and Tungsten on Methane Yields, Cell Count, and Microbiome

Abstract: Lignocellulosic residues, such as straw, are currently considered as candidates for biogas production. Therefore, straw fermentations were performed to quantitatively estimate methane yields and cell counts, as well as to qualitatively determine the microbiome. Six fully automated, continuously stirred biogas reactors were used: three mesophilic (41 °C) and three thermophilic (58 °C). They were fed every 8 h with milled wheat straw suspension in a defined, buffered salt solution, called ‘synthetic manure’. Tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
(185 reference statements)
1
4
0
Order By: Relevance
“…Contrarily, R9 and R10 with the highest methane yields, were found to contain the highest concentrations of Zn. These results confirm the positive influence of Zn on enzymes such as coenzyme M. methyltransferase , involved in methanogenesis [ 78 ]. Similarly, optimum concentrations of Ni in R5 (0.043 mg/L), R7 (0.033 mg/L), R8 (0.027 mg/L), R9 (0.053 mg/L) and R10 (0.022 mg/L) significantly increased their methane yields ( Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Contrarily, R9 and R10 with the highest methane yields, were found to contain the highest concentrations of Zn. These results confirm the positive influence of Zn on enzymes such as coenzyme M. methyltransferase , involved in methanogenesis [ 78 ]. Similarly, optimum concentrations of Ni in R5 (0.043 mg/L), R7 (0.033 mg/L), R8 (0.027 mg/L), R9 (0.053 mg/L) and R10 (0.022 mg/L) significantly increased their methane yields ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…Arthur et al [ 78 ] reported an increase in the number of methanogens present in reactors containing nickel. The author also documented that nickel concentration of less than 0.1 mg/L improved the stability of the anaerobic digestion process because intermediary products were readily digested by methanogens [ 78 ]. Further, Schmidt et al [ 79 ] reported a rapid accumulation of VFAs when Ni was depleted.…”
Section: Resultsmentioning
confidence: 99%
“…The large presence of Cloacimonadia in MABR2-S1 was likely due to the initial air supply into the membrane, as previous studies suggested the Cloacimonadia preferences to microaeration conditions. 30,31 In addition, Cloacimonadia is a syntrophic microorganism which can hardly survive without obligatory syntrophism with other microorganisms. 32 In this study, Synergistia, another syntrophic bacterium, 32 was likely to be the key contributor along with Cloacimonadia in MABR2-S1.…”
Section: Dominant Microbial Taxa and Their Relationship With Loading ...mentioning
confidence: 99%
“…In the present research, an industrial-scale method for WP preparation was used. WP was simultaneously dried and micronized with a TurboRotor mill-dryer, which is well-established in the food industry; e.g., for milling spices [36]. This method is characterized by high throughputs enabling upscaling [37] and its suitability for processing temperature-sensitive materials, such as phenolic compounds, due to its very short residence times and reduced thermal stress compared to conventional methods [38].…”
Section: Introductionmentioning
confidence: 99%